Current trends in irish infant and paediatric mortalities. (4th April 2011) - McGarvey, C; Hamilton, K; O'Regan, M; Nicholson, A; Matthews, T
Abstract : Background: There is currently limited accurate data available on the circumstances and causes of death in >1 year. Such information is needed to identify high risk groups, the most prevalent causes of death and identification of possible risk factors before interventions and their delivery can be planned. Aims: To develop a system for categorising paediatric deaths in Ireland, to examine trends in paediatric mortality (<15 years) in Ireland from 1994 to date and compare with most recent international statistics. Methods: Details of all registered deaths <15 years are forwarded to the National SIDS register by the Central Statistics Office. Following decryption data was categorised as age specific child mortality by year, the major cause of death categories in each age group, further categorised by gender. Results: At 3.2/1000 livebirths in 2008, the infant mortality in Ireland, is one of the lowest worldwide, lower than the EU average of 4.6. Conversely, in a ranking of European country child mortality (<18 years), a recent OECD report placed Ireland near the bottom of their list at 6.5 deaths per 10 000 corresponding population. The leading causes of death in children aged 4 weeks–1 year are SIDS (34.7%) and congenital anomalies (33.3%). After age 1 year, the major contributing category of death is injury and poisoning; 25% (1–4 years), 27.9% (5–15 years). Every year more males died than females and this was particularly true of deaths from injury and poisoning (68%). Head and neck injuries sustained during RTAs accounted for most of these deaths (38%) along with injuries from falls (12%) and accidental strangulation (15%). Accidental deaths occurred most frequently in the 1–4 years (46%) and 10–14 years (38.5%) age groups. The incidence of sudden unexplained deaths >1 year has increased significantly; from 1.8 cases/annum in 1994–2000, to 3.6 cases/annum in 2001–2007. Conclusions: This core dataset provides valuable information on the national paediatric population (<15 years) enabling trends and events in a number of pertinent areas such accidental and sudden unexplained deaths to be tracked annually in a timely manner. Further development of this national database, to include additional epidemiological information will assist in the development of appropriate intervention policies.